Nanocrystalline CaWO4 and ZnWO4 Tungstates for Hybrid Organic–Inorganic X-ray Detectors - Pudža, Inga; Pudžs, Kaspars; Tokmakovs, Andrejs; Strautnieks, Normunds Ralfs; Kalinko, Aleksandr; Kuzmin, Alexei (MDPI, 2023)
Hybrid materials combining an organic matrix and high-Z nanomaterials show potential for applications in radiation detection, allowing unprecedented device architectures and functionality. Herein, novel hybrid organic–inorganic systems were produced using a mixture of tungstate (CaWO4 or ZnWO4) nanoparticles with a P3HT:PCBM blend. The nano-tungstates with a crystallite size of 43 nm for CaWO4 and 30 nm for ZnWO4 were synthesized by the hydrothermal method. Their structure and morphology were characterized by X-ray diffraction and scanning electron microscopy. The hybrid systems were used to fabricate direct conversion X-ray detectors able to operate with zero bias voltage. The detector performance was tested in a wide energy range using monochromatic synchrotron radiation. The addition of nanoparticles with high-Z elements improved the detector response to X-ray radiation compared with that of a pure organic P3HT:PCBM bulk heterojunction cell. The high dynamic range of our detector allows for recording X-ray absorption spectra, including the fine X-ray absorption structure located beyond the absorption edge. The obtained results suggest that nanocrystalline tungstates are promising candidates for application in direct organic–inorganic X-ray detectors.--//-- This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).
The experiment at the DESY PETRA-III synchrotron was performed within project No. I-20211105 EC at the Institute of Solid State Physics, University of Latvia, as the Cen ter of Excellence has received funding from the European Union’s Horizon 2020 Framework Pro gramme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; tungstates; hybrid organic–inorganic X-ray detectors; X-ray sensing